PERAN PASAR LINGSIR WENGI DALAM MENGATASI KETERGANTUNGAN MASYARAKAT TERHADAP BANK PLECIT PERSPEKTIF MAQASHID SYARIAH - Purnomo, Hari; Nurul Hidayah; Rahmah Maftuhah Rohman (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2026)
Limited access to formal capital for Micro, Small, and Medium Enterprises (MSMEs) in rural areas often drives dependence on Bank Plecit (informal usurious lenders) with high-interest rates (riba), which structurally damages community economic welfare. This study focuses on analyzing the role and optimalization of the Lingsir Wengi Market program in Temuguruh Village as a community-based initiative to overcome this debt trap, examined through the perspective of the five fundamental principles of Maqashid Syariah. This research employed a qualitative approach with case study and phenomenology designs, where data was collected through participant observation, in-depth interviews, and documentation involving market managers and MSME actors. The main results indicate that the Lingsir Wengi Market plays a critical role in increasing traders' income stability and serves as an effective economic defense mechanism. The market's optimization fundamentally realizes Hifz al-Mal (protection of wealth) through legitimate transactions and Hifz an-Nasl (protection of progeny) through ensuring a decent livelihood, which is this research's significant contribution. The implication is that this sharia-based MSME market model is a practical solution for rural consumer debt issues, requiring institutional strengthening (e.g., access to micro sharia financing) to ensure sustainability. Keywords : Lingsir Wengi Market, Informal Usurious Lender, Maqashid Syariah.